Triangular shaped silicon nanowire FET characterization using COMSOL multiphysics - Yazeer, Mohamed Jameel; Za’bah, Nor Farahidah; Alam, A.H.M. Zahirul (IEEE, 2016)
The demands and expectations of high performance devices using Field Effect Transistors (FETs) are increased day by day. In order to obtain transistors with smaller size but with increased speed and performance, device scaling was done. However, making transistor in smaller size is not an easy task. One of the challenges with scaling the size of transistor is the short channel effects (SCEs). In order to reduce short channel effects, non-classical FETs were introduced. On top of that, the next transistor technology that was looked into was the semiconductor nanowire FET. In this work, a triangular shaped silicon nanowire (Si NW) FET with 300 nm channel length was designed using latest finite element analysis tool COMSOL Multiphysics and its SCE parameters were measured. The designed triangular shaped Si NW FET shows better performance in reducing the SCEs when compared with a similar sized cylindrical shaped Si NW FET and commercial MOSFET, (ZVNL120A).